Cerebrospinal fluid shunt dynamics in patients with idiopathic adult hydrocephalus syndrome. Issue 6 (June 1995) - Malm, J; Kristensen, B; Fagerlund, M; Koskinen, L O; Ekstedt, J
Abstract : The objective was to assess CSF dynamics of different shunt constructions in patients with adult hydrocephalus syndrome and correlate these findings to clinical outcome, neuroradiology, and the specifications of the shunts provided by the manufacturer. Thirty four patients with idiopathic adult hydrocephalus (normal pressure hydrocephalus) syndrome were included in a prospective, consecutive case series. A differential pressure valve (Cordis Hakim standard system) was used in 28 patients and a variable resistance valve (Cordis Orbis-Sigma) in six. A constant pressure infusion method was used; CSF pressure and conductance were determined before surgery. Three months after shunt placement CSF pressure, the "pressure v flow" curve, and gravity induced flow were measured. There was no difference between mean preoperative and postoperative resting CSF pressures in patients with Hakim shunts. The opening pressures of the Hakim shunts were higher than the value proposed by the manufacturer. A pronounced gravity effect induced CSF flow and decrease of the CSF pressure. In functioning variable resistance valves, CSF dynamics normalised postoperatively. There was no gravity effect and the characteristics shaped "pressure v flow" curve was sometimes seen. Six patients (three differential pressure valves, three variable resistance valves) had non-functioning shunts. Four of these patients were improved after the operation but improvement was transient in three. In all patients, there was no relation between the width of the ventricles and clinical improvement or CSF pressure. In conclusion, the differential pressure valve system does not behave according to the specifications provided by the manufacturer. A decrease in CSF pressure in patients with this shunt was solely due to the effect of gravity. Eleven percent of the differential pressure valves and 50% of the variable resistance valves were non-functioning. In the functioning variable resistance valves, the antisiphon system seems to be effective.